Development of A Web Based Chronic Drug Claims Management Information System Using the Fast (Framework for the Applications of Systems Thingking) Methodology - Rr. Devi Noviana Setyoningsih; Cahya Tri Purnami; Antono Suryoputro Yudhy Dharmawan; Aris Puji Widodo (Indonesian Journal of Global Health Research, 2025)
Delays of chronic drug claims caused delayed payments to the next period. The impact was disrupting the hospital's cash flow, delaying employee incentives, and creating difficulty in providing chronic drugs needed by patients. To address these operational challenges, RSUD Kajen seeks to implement a computerized drug claims information. This system will streamline processes, resolve existing inefficiencies, and improve overall patient care delivery while ensuring timely claims submission. The implementation of a computerized drug claims information system successfully facilitates claims management and improves services at RSUD Kajen.". The development of the chronic drug claims information system will be conducted using the FAST (Framework for the Applications of Systems Techniques) method. The data collection techniques employed in this research for developing the final assignment include observation, interview and literature study.  The data analysis method used is: qualitative Analysis. Qualitative analysis employs content analysis to summarize and obtain an overview of the interview and observation results, which consist primarily of qualitative data based on a conceptual framework. The results of this analysis are used to create a system design that meets users' needs. The result is a comprehensive information system that has been successfully implemented for claims management at RSUD Kajen. This information system was developed using Java programming language and MySQL database management system. System testing results demonstrate that the information system effectively accelerates the claims management process, enhances chronic drug inventory management, and generates comprehensive managerial and financial reports. A new website-based chronic drug claims management information system has been developed using the FAST method to replace the manual system. The purpose of this study is to develop a claims management information system based on user needs analysis.